2017
DOI: 10.1038/s41598-017-00445-9
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis of Genes Involved in Dendrobine Biosynthesis in Dendrobium nobile Lindl. Infected with Mycorrhizal Fungus MF23 (Mycena sp.)

Abstract: Content determination and microscopic observation proved that dendrobine accumulation in the stem of Dendrobium nobile Lindl. increased after infection with mycorrhizal fungus MF23 (Mycena sp.). Large-scale transcriptome sequencing of symbiotic and asymbiotic D. nobile revealed that 30 unigenes encoding proteins were possibly related to the biosynthesis of dendrobine sesquiterpene backbone. A qRT-PCR experiment of 16 unigenes, selected randomly, proved that there were significant changes in the expression leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
94
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(95 citation statements)
references
References 52 publications
1
94
0
Order By: Relevance
“…Employing transcriptomic approaches to collect and analyze bioinformation for understanding its genetic makeup and biosynthetic pathways of important secondary metabolites is a practical way to better protect and utilize this medicinal resource by using biotechnologies to produce products of interest in the future. By far, studies on genomic and transcriptomic level of Dendrobium plants have been confined to a few species such as D. officinal and D. nobile [13,15,16]. To our best knowledge, no transcriptomic report on D. huoshanense was retrieved up to date.…”
Section: Digital Signaturementioning
confidence: 97%
See 1 more Smart Citation
“…Employing transcriptomic approaches to collect and analyze bioinformation for understanding its genetic makeup and biosynthetic pathways of important secondary metabolites is a practical way to better protect and utilize this medicinal resource by using biotechnologies to produce products of interest in the future. By far, studies on genomic and transcriptomic level of Dendrobium plants have been confined to a few species such as D. officinal and D. nobile [13,15,16]. To our best knowledge, no transcriptomic report on D. huoshanense was retrieved up to date.…”
Section: Digital Signaturementioning
confidence: 97%
“…Moreover, dendrobine also exhibits antipyretic, hypertensive, and antiviral effects [8]. Although several groups have reported racemic and enantioselective syntheses for this compound during the past five decades [9][10][11][12], study on its biosynthetic pathway remains limited [13,14].…”
Section: Digital Signaturementioning
confidence: 99%
“…The symbiosis between Dendrobium nobile and Mycena sp. MF23 caused the accumulation of dendrobine and polysaccharide [14,15]. Mycena sp.…”
Section: Introductionmentioning
confidence: 99%
“…The active medicinal ingredients in D. officinale include: polysaccharides, alkaloids, phenols, terpenes, flavonoids and bibenzyl [9][10]. In Dendrobium plants, the content of sesquiterpene alkaloid is the main measure of its quality and medicinal efficacy [11][12]. Notably, previous studies have found that bibenzyl compounds (belonging to sesquiterpene alkaloids) might be the only bioactive ingredients in D. officinale [13][14].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, based on transcriptomic analysis, several putative rate-limiting enzyme genes responsible for the biosynthesis of terpenoids in Eugenia uniflora [32], lignin in Apium graveolens [33], and flavonoid in Phyllanthus emblica, Dracaena cambodiana, and Solanum viarum [34][35][36] have been identified. For Dendrobium plants, several studies have reported on flavonoid biosynthetic pathway analysis and the gene mining of key enzymes [37] as well as alkaloid biosynthetic pathway analysis and the identification of key enzyme genes [12,[38][39]. However, the bibenzyl biosynthetic pathway and the potential genes responsible for regulating bibenzyl biosynthesis in Dendrobium plants remain underexplored.…”
Section: Introductionmentioning
confidence: 99%